﻿HPLC-FLD analysis of amino acids content in Chrysanthemum morifolium - Alona Savych; Olha Polonets; Liubov Morozova; Kateryna Syrovatko; Tetiana Recun (Pharmacia, 2022)
Chrysanthemum morifolium (Asteraceae family) have long been used as a tonic, antioxidant, antipyretic, analgesic, sedative, antitumor, neuroprotector, hepatoprotector and cardioprotector agent. This species should be reconsidered as possible sources of many biocompounds, especially amino acids. Thus, the aim of this study was to validate the chromatographic method for detection of amino acids and their identification in flowers and leaves of Ch. morifolium of variant Pectoral. HPLC-FLD method was evaluated in terms of linearity, precision, repeatability, accuracy, LOD and LOQ. The calibration curves of all analytical standards of amino acids were linear (R2 > 0.99) over the range of 0.015–0.625 μmol/mL, the LODs and the LOQs were in the range of 0.001–0.096 µg/mL and 0.004–0.321 µg/mL, respectively. During the HPLC-FLD assay ten amino acids in free form and fifteen amino acids after hydrolysis in Ch. morifolium flowers were identified. Besides, twelve amino acids were detected in free form and fourteen amino acids after hydrolysis in Ch. morifolium leaves. The results of HPLC-FLD analysis showed that the predominant amino acid was L-proline in both types of herbal raw materials. Its total content was 31.67±0.02 μg/mg in Ch. morifolium flowers and 18.56±0.02 μg/mg in Ch. morifolium leaves. This phytochemical study confirms that flowers and leaves of Ch. morifolium (Pectoral) are rich sources of amino acids and can exhibit a wide range of pharmacological activities.